PURIFICATION RITUALS IN SHINTOISM - Hüsamettin KARATAŞ (Fırat University, 2020)
Purification in the Shinto religious tradition, It is an act of cleansing from any material and spiritual pollution before any communication and contact with the holy. In Shintoism, the Kamis are at the center of divinity. So they are pure and clean. Those who will approach the Kami and Kamis areas must also be purified. Purification ritual has both physical and psychological dimensions. According to Shintoists, purification actions such as Oharae, Misogi and Temizu in the Kamis sphere facilitate the purification of the soul's passions as well as the manifestation of the sacred, as well as body pollution. The main purpose of this research is to reveal the understanding and actions of purification in Shinto religion; as well as information from the sources based on our observations is to pass on to the reader.